Surface Characterization and Tribological Performance of Anodizing Micro-Textured Aluminum-Silicon Alloys - Luanxia Chen (Materials, 2019)
Eutectic aluminum-silicon alloys present high frictional coefficient and a high wear rate due to the low hardness under sliding friction conditions. In this paper, the eutectic aluminum-silicon alloy was textured firstly by micro-milling operations. Then, the micro-textured specimen was subjected to anodizing to fabricate alumina films. The surface topography, surface roughness, and bearing area ratio of micro-textured and anodizing micro-textured specimens were measured and characterized. For the anodizing micro-textured specimens, the surface roughness and superficial hardness increase compared with those for micro-textured ones. Tribological tests indicate that anodizing micro-textured samples present lower friction coefficient of 0.37 than that of flat samples of 0.43 under dry sliding conditions. However, they exhibit higher friction coefficient at 0.16 than that of flat samples of 0.13 under oil-lubricated conditions. The difference between the friction coefficient of anodizing micro-textured and flat samples under dry and oil-lubricated conditions is ascribed to the influence mechanism of surface roughness, bearing area ratio curves, and its relative parameters on the tribological performance of testing samples. The dry sliding friction coefficient has a positive correlation with bearing area ratio curves, while they present negative correlation with bearing area ratio curves under oil-lubricated conditions. The synergy method treated with micro-milling and anodizing provides an effective approach to enhance the dry sliding friction property of eutectic aluminum-silicon alloys.